2022
DOI: 10.1002/ps.7186
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of gut microflora across the life cycle ofSpodoptera frugiperdaand its effects on the feeding and growth of larvae

Abstract: BACKGROUND: Spodoptera frugiperda is an important invasive agricultural pest that causes huge economic losses worldwide. Gut microorganisms play a vital role in host feeding, digestion, nutrition, immunity, growth and insecticide resistance. Illumina high-throughput sequencing was used to study the gut microbial community dynamics across the life cycle (egg, 1st to 6th instar larvae, pupae, and male and female adults) of S. frugiperda fed on maize leaves. Furthermore, the gut microbial community and food intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…FAW undergoes a complete metamorphosis in which a radical anatomical restructuring of the insect occurs, accompanied by functional and lifestyle changes ( Chen et al, 2016 ). These changes can severely impact the composition of the microbiota during the different stages of its biological cycle ( Paniagua et al, 2018 ; Li et al, 2022 ; Fu et al, 2023 ; Lü et al, 2023 ). This study investigated the composition of microbial communities throughout the biological cycle of FAW corn and rice strains using high-throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FAW undergoes a complete metamorphosis in which a radical anatomical restructuring of the insect occurs, accompanied by functional and lifestyle changes ( Chen et al, 2016 ). These changes can severely impact the composition of the microbiota during the different stages of its biological cycle ( Paniagua et al, 2018 ; Li et al, 2022 ; Fu et al, 2023 ; Lü et al, 2023 ). This study investigated the composition of microbial communities throughout the biological cycle of FAW corn and rice strains using high-throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus is a genus of lactic acid bacteria with high metabolic and adaptive versatility ( Ramsey, Hartke & Huycke, 2014 ). This genus is commonly found in the gut of several Lepidoptera species ( Paniagua et al, 2018 ; Mason et al, 2020 ; Fu et al, 2023 ; Jeon et al, 2023 ; Han et al, 2023 ), and it has been reported as the dominant taxon in the gut Lepidoptera such as S. littoralis ( Chen et al, 2016 ), S. exigua ( Gao et al, 2019 ), Manduca sexta ( Brinkmann, Martens & Tebbe, 2008 ), Helicoverpa armigera ( Xiang et al, 2006 ), Lymantria dispar ( Broderick et al, 2004 ), and in S. frugiperda ( Higuita-Palacio et al, 2021 ; Li et al, 2022 ; Lü et al, 2023 ; Fu et al, 2023 ; Jeon et al, 2023 ; Han et al, 2023 ; Oliveira & Cônsoli, 2023 ). The persistence of Enterococcus throughout the life cycle of FAW suggests that this bacterium possesses efficient adaptive mechanisms that allow it to remain through different FAW developmental stages, and therefore, it might be vertically transmitted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the laboratory, antibiotics are widely used in establishing sterile or microbiota‐altered host strains to explore the functions of symbiotic bacteria 22–28 . In ticks, antibiotic treatments have allowed us to clarify the contributions of symbiotic bacteria to tick development and survival.…”
Section: Introductionmentioning
confidence: 99%
“…In the laboratory, antibiotics are widely used in establishing sterile or microbiota-altered host strains to explore the functions of symbiotic bacteria. [22][23][24][25][26][27][28] In ticks, antibiotic treatments have allowed us to clarify the contributions of symbiotic bacteria to tick development and survival. For example, the ticks Amblyomma americanum, 24 Rhipicephalus haemaphysaloides, 25 Rhipicephalus sanguineus, 26 Rhipicephalus microplus 27 and H. longicornis 28 had reduced loads of Coxiella after antibiotic treatment, and the tick hosts showed blood-feeding and developmental abnormalities, confirming the essential role of Coxiella in these tick species.…”
Section: Introductionmentioning
confidence: 99%